2019
DOI: 10.1021/acsami.9b07907
|View full text |Cite
|
Sign up to set email alerts
|

Expanded Graphite-Polyurethane Foams for Water–Oil Filtration

Abstract: Herein, expanded graphite is successfully combined with waterborne polyurethane to develop porous foams with underwater oleophobic properties for the separation of surfactant-free, oil-in-water mixtures and emulsions. To obtain foams with different pore sizes and therefore with different performances in the oil−water filtration process, two solvent-free fabrication processes are adopted. In the first one, the expanded graphite granules are mixed with the waterborne polyurethane (PUEGr), and in the second metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 72 publications
1
28
0
Order By: Relevance
“…MIP analysis allows for the quantification of detailed parameters about the macro-structures (>10 nm) of the materials, while N 2 physisorption analysis was adopted to investigate the structural characteristics of the mesoscopic (2–50 nm) and microscopic (<2 nm) pores. 51 The MIP pore-size distribution analysis revealed that the increasing concentration of pyrrole used to prepare the PPCs results in a shift toward a larger modal macropore-size ( Figure S7 ). Specifically, the pores with sizes between 0.01 and 1 μm, which are initially present in PSA, are absent in PPC10 and PPC20, while only pores larger than 100 μm remain for PPC30.…”
Section: Resultsmentioning
confidence: 99%
“…MIP analysis allows for the quantification of detailed parameters about the macro-structures (>10 nm) of the materials, while N 2 physisorption analysis was adopted to investigate the structural characteristics of the mesoscopic (2–50 nm) and microscopic (<2 nm) pores. 51 The MIP pore-size distribution analysis revealed that the increasing concentration of pyrrole used to prepare the PPCs results in a shift toward a larger modal macropore-size ( Figure S7 ). Specifically, the pores with sizes between 0.01 and 1 μm, which are initially present in PSA, are absent in PPC10 and PPC20, while only pores larger than 100 μm remain for PPC30.…”
Section: Resultsmentioning
confidence: 99%
“…[7,11] Most of the soft segments in waterbased polyurethanes are derived from petroleum-based polyols. [12,13] Therefore, there is a growing interest in using renewable resources to develop sustainable polymers. Renewable resources suitable for recycling or biodegradation as a partial or entire replacement of petroleum-based starting materials have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Polyurethane is one of the six most widely used plastic materials in the world [7,11] . Most of the soft segments in water‐based polyurethanes are derived from petroleum‐based polyols [12,13] . Therefore, there is a growing interest in using renewable resources to develop sustainable polymers.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, oil and organic solvent spills have caused worldwide concern due to the ensuing environmental pollution [1][2][3][4]. Thus, separating and recovering oil from water is becoming more and more important.…”
Section: Introductionmentioning
confidence: 99%